Review of the taxonomic revision of Chlorella and consequences for its food uses in Europe - Champenois, Jennifer; Marfaing, Hélène; Pierre, Ronan (Journal of applied phycology, 2015)
Since the discovery of the type species Chlorella vulgaris in 1890 by Beijerinck, a large number of coccoid green algae have been isolated and assigned to the genus Chlorella Beij. primarily on the basis of morphologic similarities. Based on literature review and a survey of curators of algae culture collections, our study aims to review and organize the taxonomy of Chlorella to correlate with the commercial names currently in use in Europe for food products. In particular, an inventory of the specific species or strains of Chlorella traditionally consumed in Europe is made. Chlorella pyrenoidosa , C. vulgaris , and Chlorella luteoviridis are the three species of Chlorella listed in the Novel Food Catalogue as having been on the market and consumed before 15 May 1997, and hence not subject to the Novel Food Regulation. However, as a consequence of revisions of the systematics of Chlorella , it appears that these names are not always in conformance with the current taxonomy. This is the case for the taxon C. luteoviridis which is no longer valid as it has been renamed as Heterochlorella luteoviridis . Furthermore, the review of revisions operated in algal culture collections shows that some strains had been incorrectly identified as C. pyrenoidosa or C. vulgaris . This result suggests that other species, which were known as C. pyrenoidosa or C. vulgaris at that time, might have been consumed in Europe before 1997. Therefore, the list of Chlorella species not subject to the Novel Food Regulation could possibly be extended to additional species not only strictly related to “true” Chlorella genus.